Surface chemistry modifications of rice husk toward enhancement of Hg(II) adsorption from aqueous solution - Song, Shiow-Tien (Springer, 2014)
The modified rice husks were characterized in terms of morphology (scanning electron microscopy), functional groups (Fourier transform infrared spectroscopy), surface charge (pH(pzc)), and elemental composition which indicate the treatments that led to significant changes to its surface chemistry. Batch adsorption studies showed that the highest adsorption capacity of Hg(II) was 89 and 118 mg/g obtained by sulfur-functionalized rice husk (RH-CS) and organosilane-grafted rice husk (RH-GM), respectively. The reusability of raw rice husk (RH-Raw) and alkali-treated rice husk (RH-NaOH) was superior to RH-CS and RH-GM; even though their adsorption capacities were slightly lower. However, their selectivity was comparable to that of the RH-CS and RH-GM. In addition, the results demonstrated the potential application of rice husk-based adsorbents for treating Hg(II) containing wastewaters such as produced water from oil and gas exploration activities.